Tsg101 mimicry of canonical E2 enzymes underlies its role in ubiquitin signaling - David A. Nyenhuis; Susan M. Watanabe; Nico Tjandra; Carol A. Carter (Proceedings of the National Academy of Sciences, 2025)
Tsg101 is a highly conserved protein best known as an early-functioning component of cellular ESCRT machinery participating in recognition, sorting, and trafficking of cellular cargo to various intracellular destinations. It shares sequence and structural homology to canonical ubiquitin-conjugating (E2) enzymes and is linked to diverse events regulated by Ub signaling. How it might fulfill these roles is unclear. Here, we show that Tsg101 E2 mimicry permits interactions with diverse ubiquitin ligating (E3) enzymes and underlies its multifunctional capabilities. Coexpression of Tsg101 with the E3 ligase NNedd4-2s protected the enzyme from degradation and, remarkably, other widely divergent ligases as well. Structural alignment with UbcH5, a canonical E2 enzyme, revealed that recognition at the E2-E3 interface, a region broadly conserved despite sequence and structural differences in both E2 and E3 enzymes, was critical for protection. Nevertheless, UbcH5 failed to protect NNedd4-2s, indicating that the UEV chaperone function is unique to the variant. Studies using Cy5-Ub-VME showed that Tsg101-mediated protection reduced accessibility to Cys residues in the ligase. Access to Tsg101 Ub-binding sites was critical: Rabeprazole, which interferes with Tsg101 Ub-binding, diminished E3 ligase protection. Thus, E2 mimicry permitting control of E3 ligase ubiquitin signaling underlies Tsg101’s broad ability to participate in multiple cellular functions. The study provides mechanistic insight into how Tsg101, by partnering with diverse E3 ligases, can contribute to a broad range of cellular activities.